Substitution Local Resources Basalt Stone Scoria Lampung, Indonesia, as a Third Raw Material Aggregate to Increase The Quality of Portland Composite Cement (PCC) - ., Rajiman; W Alisjahbana, Sofia; Riyanto, Hery; Hasyim, Cholil; Ikhsan Setiawan, Muhammad; Harmanto, Dani; Barid Nizarudin Wajdi, Muh (International Journal of Engineering and Technology, 2018)
Domestic cement demand is increasing in line with the increase of development of property sector and construction sector. Cement is one of the important components in making a permanent building. The function of cement in a construction is as an adhesive material that affects the strength of a building. The process of making cement is divided into two groups, namely hydraulic cement and non-hydraulic cement. Hydraulic cement consists of Portland type cement and PCC type cement, PPC cement and slag cement. The type of PCC cement (Portland Composite Cement) is produced from grinding clinker with gypsum with the addition of third raw material. The purpose of this research is to know the effect of cement quality improvement with substitution of basalt scoria stone raw material as much as 0-10% as the third raw material. The source of basalt scoria stone originated from Lampung Timur, Indonesia. The fineness test showed cement fineness was 2983-3665 cm2/gr with minimum SNI standard 2800 cm2/gr. Residue test meets the requirements of SNI standard that is equal to 16,07% -18,55%. The compressive strength test was performed at ages 3, 7 and 28 days and obtained the result that the optimum compressive strength produced was 235, 314, 394 kg/cm2. Basalt rock usage as substitution material in cement production can decrease environmental pollution caused by clinker production. Based on the cost estimation analysis, the use of basalt stone can decrease the production cost which impact on the increase of profitÂ